5 year retrospective follow-up of new cases of Charcot neuroarthropathy—A single centre experience. Issue 3 (September 2016) - Stark, C.; Murray, T.; Gooday, C.; Nunney, I.; Hutchinson, R.; Loveday, D.; Dhatariya, K.
Highlights: The recommended gold standard treatment for a Charcot joint is immobilisation. Few data describe the history of Charcot joints in a total contact plaster cast. This data represents a large single centre experience of 50 consecutive Charcot cases. Time to healing was not different between total contact cast and removable boot. Despite optimal treatment with offloading and immobilisation, 35% required recasting. Abstract: Background: Few data describe the natural history of Charcot neuroarthropathy treated with a total contact plaster cast (TCC). Methods: A 5 year retrospective analysis of 50 patients presenting with an acute CN, Assessing time to clinical resolution into appropriate footwear and assessing if initial immobilisation device influenced resolution time. Results: During the study period 42 patients (84%) of patients went into remission, 2 died during their treatment, 4 had major amputations, in 2 patients treatment was ongoing. 36 patients were treated with combination offloading devices, 6 were treated with one modality only. Median time to resolution for patients initially treated with a TCC was not significantly shorter than for those treated with a removable below knee boot. 34.9% required re-casting due to clinical deterioration in the removable device. Conclusions: More precise measures of resolution of CN are needed to assess the impact of initial treatment modality on time to resolution.